Learning from Bangladesh’s Journey Toward Ending Poverty - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, notes that Bangladesh offers us many lessons in ending extreme poverty, and one of the most important is that innovation plays a critical role. Bangladesh recognized decades ago that empowering women is essential to ending extreme poverty. Leaders arrived at the logical conclusion that countries can never reach their full economic potential if half the population is not fully participating. The World Bank Group is looking forward to working with Bangladesh to promote private sector investment by strengthening governance and improving the investment climate. Now, foreign direct investment is less than 1.7 percent of GDP in Bangladesh, far below that of most countries; foreign direct investment in Vietnam, for instance, was 6.1 percent of GDP. Strengthening governance will help lead to more jobs in infrastructure, diversify exports, and ensure the health and safety of workers. Bangladesh has shown the world that a long list of hardships can be overcome. In fact, its people have shown that innovation, commitment, setting goals, and visionary leadership can accomplish feats that few dared imagine. Bangladesh can continue to build on this record and can end extreme poverty by 2030 and boost shared prosperity.